Genetic Loci Associated With Atrial Fibrillation: Relation to Left Atrial Structure in the Framingham Heart Study. Issue 2 (2nd April 2014) - Magnani, Jared W.; Yin, Xiaoyan; McManus, David D.; Chuang, Michael L.; Cheng, Susan; Lubitz, Steven A.; Arora, Garima; Manning, Warren J.; Ellinor, Patrick T.; Benjamin, Emelia J.
Abstract : Background: Atrial fibrillation (AF) results in significant morbidity and mortality. Genome‐wide association studies (GWAS) have identified genetic variants associated with AF. Whether genetic variants associated with AF are also associated with atrial structure, an intermediate phenotype for AF, has had limited investigation. We sought to investigate associations between single nucleotide polymorphisms (SNPs) and atrial structure obtained by cardiovascular imaging in the Framingham Heart Study. Methods and Results: We selected 11 SNPs that have been associated with AF in GWAS. We examined the SNPs' relations to cross‐sectional left atrial (LA) dimensions (determined by transthoracic echocardiography) and LA volume (determined by cardiovascular magnetic resonance [CMR]) employing linear regression. The total sample included 1555 participants with CMR LA volume (age 60±9 years, 53% women) and 6861 participants with echocardiographic LA diameter (age 48±13 years, 52% women) measured. We employed a significance threshold of P< 0.0023 to account for multiple testing of the 11 SNPs and 2 LA measures. In a primary analysis, no SNPs were significantly related to the LA measures. Likewise, in secondary analyses excluding individuals with prevalent AF (n=77, CMR sample; n=105, echocardiography sample) no SNPs were related to LA volume or diameter. Conclusion: In a community‐based cohort, we did not identify a statistically significant association between selected SNPs associated with AF and measures of LA anatomy. Further investigations with larger longitudinally assessed samples and a broader array of SNPs may be necessary to determine the relation between genetic loci associated with AF and atrial structure.